2021
DOI: 10.5194/acp-21-13609-2021
|View full text |Cite
|
Sign up to set email alerts
|

In situ ozone production is highly sensitive to volatile organic compounds in Delhi, India

Abstract: Abstract. The Indian megacity of Delhi suffers from some of the poorest air quality in the world. While ambient NO2 and particulate matter (PM) concentrations have received considerable attention in the city, high ground-level ozone (O3) concentrations are an often overlooked component of pollution. O3 can lead to significant ecosystem damage and agricultural crop losses, and adversely affect human health. During October 2018, concentrations of speciated non-methane hydrocarbon volatile organic compounds (C2–C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 95 publications
2
22
0
Order By: Relevance
“…Whereas, O 3 production rate decreases to 1.1 ppbv hr −1 in +50% NO x case. Even though O 3 levels are lower at the suburban site, the result that O 3 level is enhanced by VOCs (but saturated by NO x ) is in agreement with another station in the Delhi region (Nelson et al., 2021). The model consists of important isoprene reactions with for example, NO 3 , O 3 , and OH (Calvert et al., 2008).…”
Section: Resultssupporting
confidence: 87%
“…Whereas, O 3 production rate decreases to 1.1 ppbv hr −1 in +50% NO x case. Even though O 3 levels are lower at the suburban site, the result that O 3 level is enhanced by VOCs (but saturated by NO x ) is in agreement with another station in the Delhi region (Nelson et al., 2021). The model consists of important isoprene reactions with for example, NO 3 , O 3 , and OH (Calvert et al., 2008).…”
Section: Resultssupporting
confidence: 87%
“…However, the majority of those reports pointed to an unusual higher concentration of O 3 during the same lockdown period in a significant number of places throughout the India [33,36]. It was generally found that the increase/decrease phenomena of photochemically processed tropospheric O 3 are complicated because of its non-linear relationship with its precursors (NO 2 or NO X and VOCs) and meteorological variables; and the reduction of precursor does not necessarily lead to a reduction in tropospheric O 3 [21]. Keeping these in mind, the present study only focuses on the tropospheric O 3 profile of 30 major cities throughout the India during the lockdown of 2020, with reference to the pre-lockdown of 2020, and the same time span of the previous years 2018 and 2019; and, with the aim to understand if the changes in O 3 profile are regional/seasonal precursor and/or meteorological variables dependent/limited or not.…”
Section: Discussionmentioning
confidence: 99%
“…In VOCs limited environment, the higher O 3 levels mostly depend on increasing VOCs and rarely on NO X ; but in NO X limited environment, the O 3 generation pattern and precursor dependence become vice-versa. It is important to determine which environment prevails before developing any O 3 management strategies [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The satellite-based urban HCHO trends are discussed and compared to the estimated AVOC emission trends in bottom-up inventories and to the respective OMI NO 2 trends calculated over the same cities. VOC and NO x are the key ingredients in the formation of tropospheric ozone (Calvert et al 2015), of which abundances have been generally increasing over East and South Asia in the last decades (Nelson et al 2021). Although road transport and other sectors contribute significantly to both AVOC and NO x emissions, the AVOC/NO x emission ratio is sectordependent and some of the major sources of NO x and AVOC (power generation and solvent use, respectively) are markedly different (Li et al 2017).…”
Section: Introductionmentioning
confidence: 99%